Culturally Designed Pedagogy in India Need for Skill Development - Singh, Chandra B. P. (JOURNAL OF INDIAN EDUCATION, 2016)
Adequate education and skills can improve the employability of workers, the productivity of enterprises and the inclusiveness of economic growth. This realisation has led to redesign pedagogy introduced at the school level and has also increased interest in the formulation of skills development policies to drive the change necessary to meet development challenges. To visualise a functional relationship between culture and pedagogy in the labour market it is desirable to ascertain pedagogy ingrained in secondary school education system. Reform efforts based on an ideal model of rationality assume that teachers would be receptive to scientific knowledge about pedagogy. They would directly apply it to their teaching. This model is etic (universal) by nature and known as process product paradigm. The lack of acknowledgement and appropriation of universal best practices of instruction by teachers led to indigenous pedagogical approach which is more contextual and local. This conceptual paper attempts to capture cultural realities in the context of skill development programme.